IFNγ and TNFα synergistically induce apoptosis of mesenchymal stem/stromal cells via the induction of nitric oxide - Xiaolei Li (Stem Cell Research & Therapy, 2019)
Abstract Background Mesenchymal stem/stromal cells (MSCs) have been widely used to treat various inflammatory diseases. The immunomodulatory capabilities of MSCs are usually licensed by inflammatory cytokines and may vary depending on the levels and the types of inflammatory cytokines. However, how the inflammatory microenvironment affects the fate of MSCs remains elusive. Here we characterized the molecular mechanism underlying the apoptosis of mouse MSCs triggered by the synergistic action of IFNγ and TNFα. Methods We isolated and expanded MSCs by flushing the femoral and tibial bone marrow of wild-type, iNOS−/−, and Fas−/− mice. BM-MSCs were treated with IFNγ and TNFα in vitro, and cell viability was evaluated by a CCK-8 kit. Apoptosis was assessed by Annexin V/propidium iodide-stained flow cytometry. Expression of genes related to apoptosis and endoplasmic reticulum (ER) stress was measured by reverse transcription-polymerase chain reaction (RT-PCR). Apoptosis and autophagy-related proteins were examined by Western blot analysis. Results IFNγ and TNFα synergistically trigger apoptosis of mouse BM-MSCs. The two cytokines were shown to stimulate the expression of inducible nitric oxide synthase (iNOS) and consequently the generation of nitric oxide (NO), which is required for the apoptosis of mouse BM-MSCs. The two cytokines similarly induced apoptosis in Fas−/− BM-MSCs. iNOS and NO were shown to upregulate Fas in mouse MSCs and sensitize them to Fas agonist-induced apoptosis. Moreover, NO stimulated by IFNγ/TNFα impairs autophagy, which aggravates ER stress and promotes apoptosis. Conclusions IFNγ/TNFα-induced apoptosis in mouse MSCs is mediated by NO. Our findings shed new light on cytokine-induced apoptosis of MSCs and have implications in MSC-based therapy of inflammatory diseases.